Pipelines 2017. proceedings of sessions of the Pipelines 2017 Conference, August 6-9, 2017, Phoenix, Arizona - Pridmore, Anna B.; Geisbush, Jim (American Society of Civil Engineers, 2017)
"This collection contains 49 peer-reviewed papers on the construction and rehabilitation of pipelines for for reliability and resiliency through sustainable design and construction. Topics include: leak detection and monitoring; lining and pipe materials; design-build alternative delivery; planning and design issues; and case studies"--ASCE website
Keywords: Pipelines -- Design and construction -- Congresses.; Pipelines -- Maintenance and repair -- Congresses.; Sustainable construction -- Congresses.; elektronické knihy; electronic books